Development of Virtual Field Trip-Based Learning Model as A Strengthening of Madrasah Student Digital Literacy - Khotimah, Sita Husnul; Krisnawati, Nofi Maria; Abusiri, Abusiri; Mubin, Fatkhul; Wardi, Moh. (Nazhruna: Jurnal Pendidikan Islam, 2024)
This article aims to determine how the development, feasibility, effectiveness, and practicality of virtual field trip (VFT)-based learning models strengthen students’ digital literacy. The research was conducted in three Madrasah Ibtidaiyah (MI) areas of South Jakarta, Bogor (West Java), and Kediri (East Java). The trial was conducted for students (sixth-grade students) in each school in one class. This research uses a qualitative descriptive approach with research and development (R&D) methods, according to Borg & Gall. Research data on the application of the model were obtained through observation, tests, and questionnaires, while data analysis was carried out through average and percent scores. This development research obtained a model design from VFT-based learning steps. Based on the results of the trial revealed that (1) the model met the Feasible criteria shown by the assessment of experts and practitioners with an excellent category; (2) the model met the Effective criteria shown by the average results of strengthening digital literacy with an excellent category, and the average results of positive responses to the implementation of learning with Agree/Happy criteria, as well as the achievement of student learning outcomes from the three trial classes obtained a percentage increase above 5%; (3) the model met the Practical criteria shown by the implementation of learning through VFT and the teacher’s ability to manage the learning with an excellent category. The research results briefly state that the VFT-based learning model developed can reinforce students’ digital literacy.